2000
DOI: 10.1021/cm0010598
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Intensity of Luminescence Emission from Silica/Poly(ethylene oxide) and Silica/Poly(propylene oxide) Nanocomposite Gels

Abstract: Transparent nanocomposite gels have been synthesized by the sol−gel method using hybrid precursors composed of two triethoxysilane groups and a mid polyether chain [poly(ethylene oxide) or poly(propylene oxide)] of various chain lengths. The end silicate groups are linked with the polyether chain through urea bridges (Ureasils). These nanocomposite materials can be visualized as silica nanoparticles dispersed in the organic phase provided by polyether chains. The gels are important room-temperature luminescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 19 publications
5
67
0
Order By: Relevance
“…The emission spectrum shows two peaks at 310 nm, indicating the existence of two emitting polymeric species, which is different from H-PEAE-mono, H-PEAE-di and L-PEAE. A similar inherent luminescence property exhibited from silica based on sol-gel materials has been reported, pointing out the generation of emitting nanocluster species, and proved by the dependence of emission wavelength on the excitation wavelength [25,26]. Moreover, the similar inherent blue luminescence property for hyperbranched and linear polyethylenimines has also been reported, probably due to the creation of amine rich nanocluster and electron-hole recombination process [18,27].…”
Section: Fluorescence Propertiesmentioning
confidence: 54%
See 1 more Smart Citation
“…The emission spectrum shows two peaks at 310 nm, indicating the existence of two emitting polymeric species, which is different from H-PEAE-mono, H-PEAE-di and L-PEAE. A similar inherent luminescence property exhibited from silica based on sol-gel materials has been reported, pointing out the generation of emitting nanocluster species, and proved by the dependence of emission wavelength on the excitation wavelength [25,26]. Moreover, the similar inherent blue luminescence property for hyperbranched and linear polyethylenimines has also been reported, probably due to the creation of amine rich nanocluster and electron-hole recombination process [18,27].…”
Section: Fluorescence Propertiesmentioning
confidence: 54%
“…The coexistence of ether linkage and carbonyl group in H-PEAEs is essential for generating the strong fluorescence. Moreover, the coexistence of NH and C=O groups is also very important for providing the states of delocalized electron-hole recombination [25]. Furthermore, the chemical groups possess electron-donating capacity also play a key role in generating the inherent luminescence property [26].…”
Section: Fluorescence Propertiesmentioning
confidence: 99%
“…[67] As previously mentioned, defects in the silica component hybrid matrices can also be a source of luminescence, which can be tuned by the presence of inorganic chromophores. [68,69] Indeed, silica±polyethylene oxide or silica±polypropylene oxide hybrids exhibit an intense room-temperature luminescence arising from electron±hole recombination on delocalized states provided by the silica nanophase. These hybrids, doped with divalent cations or with rare-earth ions, have enhanced emission properties because the cations solubilizing close to the silica clusters decrease surface defects and the ensuing quenching mechanism.…”
Section: One-pot Synthesis Of Rare-earth-doped Hybrid Matricesmentioning
confidence: 99%
“…These hybrids, doped with divalent cations or with rare-earth ions, have enhanced emission properties because the cations solubilizing close to the silica clusters decrease surface defects and the ensuing quenching mechanism. [68,69] Direct inclusion of chelated or crypted lanthanides or lanthanide porphyrins inside sol±gel-derived matrices, or in-situ formation of the rare-earth complexes, leads to the formation of hybrid materials with generally improved luminescent properties.…”
Section: One-pot Synthesis Of Rare-earth-doped Hybrid Matricesmentioning
confidence: 99%
“…This effect agrees with several reports for silicon-based nanostructured materials indicating that the emission energy decreases with an increase in the size of the nanodomains. [13,16,17,19,[35][36][37][38][39][40][41] In particular, Bekiari and Lianos [41] showed that the PL of hybrids obtained by the interaction between (3-aminopropyl)triethoxysilane and organic acids could be tuned in the whole visible region by controlling the cluster size through the aging time. However, to the best of our knowledge this is the first report where the PL spectra of a urea-bridged silsesquioxane could be varied over such a broad spectral range, varying the conditions of the synthesis.…”
Section: Photoluminescence Of the Bridged Silsesquioxanesmentioning
confidence: 99%